The writer's agenda : the Wadsworth writer's guide - Guth, Hans Paul (Belmont, California : Wadsworth Publishing Company, 1989)
This book aims at a new synthesis of what is best in current theory and research and in current practice.
Part One. Why and how we write -- Part Two. From experience to exposition -- Part Three. Writing and thinking -- Part Four. The writer's tools -- Part Five. Special assignment.
Includes index.
Keywords: ENGLISH LANGUAGE -- RHETORIC